The Persistence of Sentiment : Display and Feeling in Popular Music of the 1970s - Morris, Mitchell, 1961- (Book collections on Project MUSE., 2013)
How can we account for the persistent appeal of glossy commercial pop music? Why do certain performers have such emotional power, even though their music is considered vulgar or second rate? The author gives a critical account of a group of American popular music performers who have dedicated fan bases and considerable commercial success despite the critical disdain they have endured. This book examines the specific musical features of some exemplary pop songs and draws attention to the social contexts that contributed to their popularity.